Simple Generation of Suspensible Secondary Microplastic Reference Particles via Ultrasound Treatment - von der Esch, Elisabeth; Lanzinger, Maria; Kohles, Alexander J.; Schwaferts, Christian; Weisser, Jana; Hofmann, Thomas; Glas, Karl; Elsner, Martin; Ivleva, Natalia P. (Frontiers in Chemistry, 2020)
In the environment the weathering of plastic debris is one of the main sources of secondary microplastic (MP). It is distinct from primary MP, as it is not intentionally engineered, and presents a highly heterogeneous analyte composed of plastic fragments in the size range of 1 μm−1 mm. To detect secondary MP, methods must be developed with appropriate reference materials. These should share the characteristics of environmental MP which are a broad size range, multitude of shapes (fragments, spheres, films, fibers), suspensibility in water, and modified particle surfaces through aging (additional OH, C=O, and COOH). To produce such a material, we bring forward a rapid sonication-based fragmentation method for polystyrene (PS), polyethylene terephthalate (PET), and polylactic acid (PLA), which yields up to 105/15 mL dispersible, high purity MP particles in aqueous media. To satisfy the claim of a reference material, the key properties—composition and size distribution to ensure the homogeneity of the samples, as well as shape, suspensibility, and aging —were analyzed in replicates (N = 3) to ensure a robust production procedure. The procedure yields fragments in the range of 100 nm−1 mm (<20 μm, 54.5 ± 11.3% of all particles). Fragments in the size range 10 μm−1 mm were quantitatively characterized via Raman microspectroscopy (particles = 500–1,000) and reflectance micro Fourier transform infrared analysis (particles = 10). Smaller particles 100 nm−20 μm were qualitatively characterized by scanning electron microcopy (SEM). The optical microscopy and SEM analysis showed that fragments are the predominant shape for all polymers, but fibers are also present. Furthermore, the suspensibility and sedimentation in pure MilliQ water was investigated using ultraviolet–visible spectroscopy and revealed that the produced fragments sediment according to their density and that the attachment to glass is avoided. Finally, a comparison of the infrared spectra from the fragments produced through sonication and naturally aged MP shows the addition of polar groups to the surface of the particles in the OH, C=O, and COOH region, making these particles suitable reference materials for secondary MP.